2021
DOI: 10.1111/mbe.12309
|View full text |Cite
|
Sign up to set email alerts
|

“Why Can't I See My Friends and Family?”: Children's Questions and Parental Explanations About Coronavirus

Abstract: Question-explanation exchanges in parent-child interactions foster children's early learning, especially when children are inquiring about unobservable scientific phenomena such as the novel coronavirus (COVID-19). As with other unobservable entities, children must rely on adults to acquire knowledge about COVID-19. Yet, we know very little about what children understand about COVID-19 or its consequences. In our study, we explored developmental changes in children's questions about COVID-19 and parents' expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…Another recent study by Haber et al (2022) examined how parents in the US explained the coronavirus to their 3-to 8-year-old children via an online survey. Parents also reported children's questions about the coronavirus.…”
Section: Children's Questions and Parent's Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent study by Haber et al (2022) examined how parents in the US explained the coronavirus to their 3-to 8-year-old children via an online survey. Parents also reported children's questions about the coronavirus.…”
Section: Children's Questions and Parent's Responsesmentioning
confidence: 99%
“…Children mostly rely on the information they receive from knowledgeable adults around them (i.e., parents, teachers) when learning about such processes (Harris, 2012;Harris & Koenig, 2006;Harris et al, 2018). The coronavirus also poses a challenging biological concept for children; it is transmitted from person to person via unobservable particles, has an incubation period, and leads to various symptoms (Haber et al, 2022). Thus, children need to solicit information from knowledgeable adults to understand the coronavirus's causes and consequences and learn how to protect themselves against the coronavirus.…”
mentioning
confidence: 99%
“…Earlier studies also indicate that young children make sense of natural phenomena using magical or animistic thinking [ 55 , 56 ]. Prior studies of explanations regarding the Coronavirus show that parents report providing correct realistic responses to children’s questions in different cultural contexts [ 41 43 ]. Haber et al [ 41 ] also showed that parents of 3-5year-olds often reference germs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Turkish parents provide explanations to their children rather than leaving the questions unattended [ 43 ], while in about half of the cases parents in the US do not provide explanations [ 42 ]. The responses children receive are realistic but mostly very general [ 41 , 42 ]. If parents provide more specific responses, then parents of younger children will reference germs in their responses, while parents of older children will be more likely to use illness analogies in their explanations [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic led children to ask questions to their parents about the virus, lifestyle changes including those related to schooling, and health and safety precautions. Research shows that parents provided informative answers to these questions (Menendez et al, 2021;Haber et al, 2022;Ünlütabak & Velioğlu, 2022).…”
Section: Children's Questions About the Covid-19 Pandemicmentioning
confidence: 99%